Survival Rates of Prostate Cancer Patients after Diagnosis in Srinagarind Hospital, Khon Kaen University - Sawangjaeng, Itsarate; Kamsa-ard, Supot; Sirithanaphol, Wichien; Santong, Chalongpon (Srinagarind Medical Journal, 2022)
Background and objective: Prostate cancer (PC) is the most common cancer in men. Previous studies have reported survival rates of PC but haven’t updated. This study aimed to determine the survival rate of PC patients who treated at Srinagarind Hospital, Faculty of Medicine, Khon Kaen University which is a tertiary hospital in the Northeast region of Thailand. Methods: A retrospective cohort study was conducted. Data were retrieved from the Srinagarind hospital-based cancer registry (2013-2017) and followed up until 2019 of 672 cases. The survival rate was estimated using the Kaplan-Meier method. We reported the median survival time and the 95% confidence interval (CI). A comparison group was used to estimate the survival rate using the Log-rank test. Result: Of 627 PC patients, a case-fatality rate of 16.0 per 100 person-years (95%CI; 14.5 - 17.7). The median survival time was 3.87 years (95%CI; 3.2 - 4.6). The respective overall survival experience rate after diagnosis at 1, 3, 5 and 7 years were 84.3 (95%CI; 81.3 - 86.9), 55.2 (95%CI; 51.2 – 59.0), 45.0 (95%CI; 41.1 - 48.9) and 37.6 (95%CI; 33.2 - 41.9) respectively. Comparing survival rate, age histological grading staging bone metastasis and surgery were different in survival between the two groups by statistically significantly. (p < 0.05) Conclusion: The survival rate of PC after diagnosis in Srinagarind Hospital was high. By early stage, the survival rate of patients over 7 years was 78.3%. Therefore, early detection screening is needed to improve survival rates and cured the disease.